2007
DOI: 10.3354/meps339025
|View full text |Cite
|
Sign up to set email alerts
|

Surface bacterial community, fatty acid profile, and antifouling activity of two congeneric sponges from Hong Kong and the Bahamas

Abstract: Bacterial communities on the surfaces of 2 congeneric sponges, Mycale adhaerens from Hong Kong and M. laxissima from the Bahamas, were compared using conventional cultivation techniques and terminal restriction fragment length polymorphism (TRFLP) analysis -a cultureindependent DNA fingerprinting technique. The bacterial community on the Hong Kong sponge was more diverse, in terms of the number and type of species isolated, and different from that on the Bahamas sponge, as evident from distinct clusters formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…The bacterial settlement field assay was adapted from similar methods described by Henrikson & Pawlik (1995), Harder et al (2004), Dobretsov et al (2005a,b), and Lee et al (2007). Extracts were re-dissolved by gentle sonication using methanol for n-butanol and Et 2 O for Et 2 O partitions to give 10-fold natural concentrations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The bacterial settlement field assay was adapted from similar methods described by Henrikson & Pawlik (1995), Harder et al (2004), Dobretsov et al (2005a,b), and Lee et al (2007). Extracts were re-dissolved by gentle sonication using methanol for n-butanol and Et 2 O for Et 2 O partitions to give 10-fold natural concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…Tsoukatou et al 2002, Dobretsov et al 2005a,b, Lee et al 2007, Qian et al 2010. One of the first steps in the fouling process is bacterial settlement and the establishment of a biofilm, which can influence the later settlement of macrofouling organisms such as barnacles and polychaetes (Sjögren et al 2004, Lau et al 2005, Lee et al 2007). Modulation or prevention of bacterial settlement is therefore a likely target for the sponge's antifouling compounds (Kubanek et al 2002, Kelly et al 2003, Lee et al 2007.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies suggest a stable and specific relationship between sponges and bacteria. However, debate on the stability and specificity of sponge-microbe association arises because of contradictory results showing variations in bacterial communities associated with sponges from different genera, locations or time scale (Qian et al, 2006;Wichels et al, 2006;Lee et al, 2007). In a more recent study, Lee et al (2009b) demonstrated that consistent bacterial communities only hold for certain species of sponges.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, crude extracts of the sponge Crella incrustans and cholesterol controls had a negative effect on the settlement of larvae of the ascidian Podoclavella moluccensis (Davis et al 1991). Finally, Lee et al (2007) suggested that the species-specific, surface-associated bacterial communities and antifouling activities of the congeneric sponges Mycale adhaerens from Hong Kong and Mycale laxissima from the Bahamas might result from the differences in the fatty acid profiles of these sponges. Mycale adhaerens has a more diverse fatty acid profile, in terms of the type and relative abundance of fatty acids detected, than M. laxissima (Lee et al 2007).…”
Section: Hexadecanoic Cholesterol Lathosterol Sitosterol Acidmentioning
confidence: 99%